DIALEKTIKA MORAL DALAM TEKS SARASAMUCCAYA - Puspo Renan Joyo (Fakultas Dharma Duta, 2020)
Moral values have a sense of urgency in human culture and civilization. As a value, moral is the means to organize life together. Especially in an era of globalization, the world becomes open and bond moral values began to weaken. Society in crisis in all fields and the most severe crisis is moral. Sarasamuccaya as one source of value in Hinduism has a spirit and synergy of the moral, and cultural dialectic. Through the hermeneutics theoretical framework, this paper seeks to interpret and display the ideas of morality in the Text Sarasamuccaya. This discussion will focus on the moral aspect of thought, speech, and behavior. Why? Because in this area the movement of moral values occurs. Thus, Sarasamuccaya, very straightforward, and technical reminds us to always consider every activity of thought, speech, and behavior in order not to deviate from the guidelines of morality. The results of this study indicate that Sarasamuccaya explains morality in three, important areas, namely thoughts, speeches, and behaviors.